The novel in life - McKeen, Sarah Laura (My University, 1895)
Intoduction: We are constantly hearing something about the novel and the influence which it has had upon people. At the present time we might say that the novel is the most universally read of all forms of literature, for it is read by all classes of people, both the educated and the uneducated. Many condemn all novels, and say their influence is evil; others condemn only a part, thinking that some are very beneficial to the reader.
Citation: McKeen, Sarah Laura. The novel in life. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Novel; People; Literature; Influence; Evil; Theses; Manuscripts (documents)